Characterization of the complete chloroplast genome of Linnaea borealis, a rare, clonal self-incompatible plant. Issue 1 (2nd January 2020) - Liu, Hairui; Xia, Mingze; Xiao, Qingmeng; Fang, Jie; Wang, Anqi; Chen, Shilong; Zhang, Dejun
Abstract: Linnaea borealis L. is a creeping shrub which grows about 5–10 cm high and is a rare clonal plant. Linnaea is a monotypic genus. Here, we release and detail the complete chloroplast genome sequences of L. borealis, whose size is 161, 576 bp, containing a large single copy region (LSC) of 85, 609 bp and a single copy region (SSC) of 46, 694 bp which typically separates by a pair of inverted repeats (IRs) of 29, 210 bp. The amount of the overall genes is 136, which includes 37 tRNA genes, eight rRNA genes, and 91 protein-coding genes. The content of the G/C in whole plastome is 61.74% while the G/C content of the LSC, SSC, and IR region are 36.58%, 38.86%, and 42.25%, respectively. The complete cp genome sequences of L. borealis will be a useful resource to the phylogenetics study in family Caprifoliaceae.